133 A QUALITATIVE STUDY ON PARENTS' PERSPECTIVES OF THE CLINICAL EXPERIENCE BEFORE, DURING, AND AFTER THE DEATH OF A CHILD. (1st January 2006) - Yi, M.; McCormick, T.; Min, D.; Conley, B.
Abstract : Introduction: The death of a child is a life-altering event for parents. However, there are limited studies in the bereavement literature regarding parents' perceptions of their experience with the medical community and their level of satisfaction with these clinical encounters. The purpose of this study was to explore the personal perspectives of parents about their clinical experiences before, during, and after the death of a child. Study Design and Methods: A descriptive, qualitative study was conducted using a structured interview guide. Participants were volunteers drawn from a grief support group in the Seattle-Tacoma area. Six couples and one single mother were interviewed at length about their interaction with the medical community surrounding the care of their children. Qualitative content analysis was used to analyze the data. Results: The following five themes emerged: (1) parental empowerment and awareness of the medical situation through communication and information; (2) components of the medical relationship that affect the development of parental trust and perception of care provided by health care professionals; (3) contributing factors in parents' ability to connect physically and/or emotionally with their child; (4) support network outside of hospital personnel: family, friends, and community groups; (5) application of potential emotional responses to loss and the transformation of parental hope for their child. It was clear that the approach to death is not intuitive to parents; they rely on communication and information from health care professionals to guide their awareness of the dying process. In addition, it seems that a shared understanding and gradual transition through the child's dying process facilitate the parent-child joining, whereas a lack of preparation for a child's death can have traumatic effects similar to PTSD. We found that as part of the grief process, parents often have the need to review the events surrounding the death of their child. In this process, it was comforting for parents to believe that they were informed and included in his/her care, that health care professionals were sincere in their care, and that everything possible was done in an effort to save their child. In contrast, recollection of negative experiences perpetuated feelings of confusion, doubt, guilt, anger, and betrayal. Conclusion: This study reinforces the importance of offering support to parents who have lost a child to death. In the clinical encounter, opportunities exist for health care professionals to influence parents and their subsequent feelings related to their grief response.